Pemikiran KH. Maimoen Zubair tentang Islam Nusantara serta Implementasinya dalam Pendidikan Pesantren - Arju Mushaffa; M. Ulul Azmi; Muhammad Thoriqul Islam; Amalia Rizki Lailatul Khilwa; Farida Nur Azizah (IIQ An Nur Yogyakarta, 2026)
This article aims to analyze KH. Maimoen Zubair’s ideas on Islam Nusantara, explain their implementation through educational practices at the Al-Anwar Islamic Boarding School, and examine their relevance to the development of Islamic education in Indonesia. This study employed a literature review method, examining various documented and published sources relevant to the topic, which were then analyzed using a descriptive-analytical approach. The research findings indicate that, in the view of KH Maimoen Zubair, Islam Nusantara serves not only as a cultural expression but also as an ethical framework for fostering religious nationalism oriented toward the common good and national unity. The relationship between Islam and nationalism is understood as complementary, while the Al-Anwar Islamic Boarding School serves as a medium for internalizing these values through Islamic educational practices. KH Maimoen Zubair’s exemplary religious character, tolerance, spirit of nationalism, and social concern have significant implications for strengthening religious moderation and character education in Indonesia.keywords: Islam Nusantara, Exemplary Religious Scholar, KH Maimoen Zubair, Religious Nationalism, Pesantren Education.